Corporate governance and cash holdings: Focusing on a corporate governance report in Korea - Kevin Troy Chua; Hansol Lee (Investment Management & Financial Innovations, 2024)
This study examines the effect of corporate governance on a company’s cash holdings, focusing on a firm’s compliance levels with core corporate governance indicators as outlined in the corporate governance report. Utilizing a random effect generalized least squares (GLS) regression model, this study evaluates 812 firm-year observations from Korean publicly traded companies covering the period 2018 to 2021. The results indicate that companies with robust governance structures generally maintain lower levels of cash holdings (coefficient = –0.0263, p-value = 0.044), corroborating the flexibility hypothesis. Moreover, higher compliance levels with governance matters concerning shareholder protection (coefficient = –0.0388, p-value = 0.090) and board of directors (coefficient = –0.0512, p-value = 0.052) are associated with reduced cash holdings. Further analysis, accounting for a firm’s organizational capital, underscores that the inverse relationship between corporate governance and cash holdings is more pronounced in organizations with lesser organizational capital (coefficient = –0.0548, p-value < 0.01). This study contributes empirical evidence showing that strict compliance with core corporate governance indicators, indicative of strong corporate governance, substantially affects a firm’s cash management. Additionally, this study offers valuable insights for regulatory authorities and investors and enhances the existing body of knowledge on the interplay between corporate governance and cash holdings.